Coefficient Bounds and Fekete–Szegö Inequalities for a Two Families of Bi-Univalent Functions Related to Gegenbauer Polynomials - Yahya Almalki; Abbas Kareem Wanas; Timilehin Gideon Shaba; Alina Alb Lupaş; Mohamed Abdalla (Axioms, 2023)
The purpose of this article is to introduce and study certain families of normalized certain functions with symmetric points connected to Gegenbauer polynomials. Moreover, we determine the upper bounds for the initial Taylor–Maclaurin coefficients <semantics>|a2|</semantics> and <semantics>|a3|</semantics> and resolve the Fekete–Szegöproblem for these functions. In addition, we establish links to a few of the earlier discovered outcomes.